Neurogenetic approaches to stress and fear in humans as pathophysiological mechanisms for posttraumatic stress disorder - Nees, Frauke; Witt, Stephanie; Flor, Herta (Biological psychiatry, 2018)
In this review article, genetic variation associated with brain responses related to acute and chronic stress reactivity and fear learning in humans is presented as an important mechanism underlying posttraumatic stress disorder. We report that genes related to the regulation of the hypothalamic-pituitary-adrenal axis, as well as genes that modulate serotonergic, dopaminergic, and neuropeptidergic functions or plasticity, play a role in this context. The strong overlap of the genetic targets involved in stress and fear learning suggests that a dimensional and mechanistic model of the development of posttraumatic stress disorder based on these constructs is promising. Genome-wide genetic analyses on fear and stress mechanisms are scarce. So far, reliable replication is still lacking for most of the molecular genetic findings, and the proportion of explained variance is rather small. Further analysis of neurogenetic stress and fear learning needs to integrate data from animal and human studies.